The reproductive system function at women athletes are training by lifting and taekwondo - Nekhanevich O.B. (Морфологія, 2010)
The purpose of investigation is studying the character and leading mechanisms of reproductive system pathology at women athletes are training by lifting and taekwondo. The object of research was the medical control at women are training in lifting and taekwondo. The results of the research have shown that the physical and psychoemotional overexertion with restriction of eating lead to adrenocorticotropic horomon considerable quantity emission which stimulates suprarenal glands and cause the development of hyperanrogenemy and ovaries functions depression. The athletes have more frequent menstrual cycle disturbances such as opsomenorrhea, oligomenorrhea and algodysmenorrhea. Typically there are changes of indices of physical development, appearance the symptoms of psychological masculinithation, hirsutism and secondary ovaries disturbance.